(untitled) - Dreyfack, Raymond (Rockville Centre, N.Y., 1982)
This book introduce the foundation a philosophy of management, the Japanese edge, the Japanese way, the American imperative, people, we-power, the workplace, beyond the bottom line...
Keywords: Quản trị công nghiệp,Industrial management; Nhật Bản,Japan